2017
DOI: 10.1080/10408398.2016.1262324
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin and capsiate could be appropriate agents for treatment of obesity: A meta-analysis of human studies

Abstract: Consumption of capsaicin or its nonpungent analogues, capsinoids has been reported to affect energy expenditure and fat oxidation, although available data are still controversial. The aim of the present study was to conduct a meta-analysis regarding the effects of these substances on energy expenditure and respiratory quotient, with special emphasis on the role of body mass index (BMI) of the participants. Medical databases were systematically searched for papers. Of the 627 trials identified, 9 provided resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 54 publications
2
52
2
2
Order By: Relevance
“…Conflicting results have been found on the properties of capsaicin and capsiate in decreasing the respiratory quotient by enhancing fat oxidation, due to the different designs of the studies, the body composition and BMI of the subjects included and the habitual consumption of chili in their diet [152][153][154]. Interestingly, the consumption of 2.56 mg of capsaicin (1.03 g of dried red chili pepper) per meal was able to mitigate the unfavorable negative energy balance effect of decrease in DIT and REE induced by a 25% caloric restriction in humans [155].…”
Section: Chili Pepper (Capsicum Species) Available Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Conflicting results have been found on the properties of capsaicin and capsiate in decreasing the respiratory quotient by enhancing fat oxidation, due to the different designs of the studies, the body composition and BMI of the subjects included and the habitual consumption of chili in their diet [152][153][154]. Interestingly, the consumption of 2.56 mg of capsaicin (1.03 g of dried red chili pepper) per meal was able to mitigate the unfavorable negative energy balance effect of decrease in DIT and REE induced by a 25% caloric restriction in humans [155].…”
Section: Chili Pepper (Capsicum Species) Available Evidencementioning
confidence: 99%
“…In mice, dietary capsaicin activated thermogenesis in WAT by up-regulating the expression of SIRT1 and PGC-1α, both of which increase the expression of UCP1 and bone morphogenetic protein-8b, resulting in energy dissipation by thermogenesis, increased EE and metabolic activity [156]. Both in mice and humans, capsaicin and capsinoids enhance energy expenditure by triggering BAT through multiple mechanisms, such as the stimulation of non-shivering thermogenesis by binding to TRPV1, stimulation of the SNS and catecholamine secretion from the adrenal gland [19,137,[152][153][154]156,157].…”
Section: Molecular Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, several preclinical and clinical studies have indicated that either capsiate alone or in combination with CAP is beneficial to counteract obesity and increase energy utilization [60][61][62][63][64]. However, the mechanisms behind such effect of CAP or capsiate still remain elusive.…”
Section: Trpv1: Capsaicin Receptormentioning
confidence: 99%
“…Because overweight and obesity are the result of a sustained imbalance between caloric intake and caloric expenditure, lifestyle changes including calorie restriction and increasing energy expenditure are the two cornerstones in their treatment. Additionally, there are commercial formulations in the market that claimed as capable of enhancing the effects of lifestyle changes with a variable degree of scientific evidence 4,5 .…”
Section: Introductionmentioning
confidence: 99%